Education needs of nurses in thrombosis and hemostasis: An international, mixed‐methods study. Issue 1 (1st November 2018) - Lazure, Patrice; Munn, James; Labbé, Sara; Murray, Suzanne; Butler, Regina; Khair, Kate; Lambing, Angela; Malone, Maura; Reiser, Thomas; Newall, Fiona
Abstract: Background: The need for a more integrated, multidisciplinary approach to care for individuals with bleeding or clotting disorders has been highlighted in recent years. Evidence‐based education adapted to nurses' needs is essential for a successful evolution. However, limited data currently exist on the clinical challenges nurses face in this specialty area. Objectives: Identify barriers and challenges faced by specialty nurses, and determine possible causes, to develop appropriate educational interventions. Methods: A mixed‐methods study, combining qualitative (semi‐structured interviews) and quantitative (online survey) data was conducted on the challenges experienced by hemostasis nurses in nine countries (Argentina, Australia, Canada, China, France, Germany, Spain, the UK, and the US), and deployed in five languages (English, French, German, Mandarin, and Spanish). Qualitative data were analyzed using thematic analysis. Quantitative data were analyzed using frequency tables, chi‐squares and standard deviations. Results: Participants (n = 234) included nurses (n = 212; n = 22 qualitative; n = 190 quantitative); and patients receiving care for bleeding or clotting conditions or their caretakers (n = 22 qualitative phase only). Through triangulated data analysis, six challenging areas emerged: (a) Understanding of von Willebrand disease (VWD); (b) Anticoagulant safety profile in specific patients; (c) Understanding the treatment of patients with inhibitors; (d) Patient risk assessments; (e) Individualization of care and communication with patients; and (f) Accessing and implementing relevant professional education. Conclusions: This needs assessment provides a comprehensive illustration of the current challenges faced by nurses in the field of bleeding and clotting disorders, and indicates where gaps in skills, knowledge or confidence would benefit from nurse‐specific educational programming.